2022
DOI: 10.21511/ppm.20(1).2022.36
|View full text |Cite
|
Sign up to set email alerts
|

Stability of production and trading companies considering their economic security

Abstract: The economic security of any company depends on its solvency and financial stability. It is also affected by uneven economic development due to the global financial crises, the impact of the COVID-19 pandemic, increased competition from industrial and commercial companies, and military conflicts. Thus, it is necessary to assess the stability of companies as a basis for their economic security, taking into account the indicators of solvency and financial stability. The paper used systematization, comparative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The war disrupts the supply of goods, causes logistical problems, and decreases energy capacities and individuals' real incomes. These are holding back the economy's recovery and worsening enterprises' expectations (Mazaraki & Zubko, 2022). Danylyshyn and Bohdan (2022) justify the model of the monetary regime during martial law.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The war disrupts the supply of goods, causes logistical problems, and decreases energy capacities and individuals' real incomes. These are holding back the economy's recovery and worsening enterprises' expectations (Mazaraki & Zubko, 2022). Danylyshyn and Bohdan (2022) justify the model of the monetary regime during martial law.…”
Section: Literature Reviewmentioning
confidence: 99%
“…У статті Мазаракі А. А. та Зубко Т. Л. [5] розглядається питання оцінювання стабільності компаній як основу їх економічної безпеки з урахуванням показників платоспроможності та фінансової стійкості для виробничо-торговельних компаній, проте даний механізм оцінки не може бути застосований до підприємств сфери гостинності. В дослідженні акцент спрямований на фінансову компоненту потенціалу підприємства, що не включає аналіз інших структурних елементів.…”
unclassified
“…The financial stability and solvency of enterprises is the key to the economic security of a company, which is influenced by many factors, such as the global financial crisis, the COVID-19 pandemic, armed conflicts, etc. (Mazaraki & Zubko, 2022). Korneyev et al (2022) concluded that the war led to the fact that the number of business representatives who completely or partially ceased their activities during the first three months of the war decreased from 75.3% in March to 49.0% in May (compared to February 24, 2022), which indicates a gradual recovery of business in Ukraine.…”
mentioning
confidence: 99%